Elemental chemical composition of wood and charcoal from Coffea arabica for bioenergy use - Leite, Edson Rubens da Silva; Protásio, Thiago de Paula; Rosado, Sebastião Carlos da Silva; Trugilho, Paulo Fernando; Valle, Mara Lúcia Agostini; de Siqueira, Humberto Fauller (Coffee Science - ISSN 1984-3909, 2015)
Coffee has a prominent position in Brazilian economy, especially in southern Minas Gerais, the main producing state. Despite extensive research involving coffee plantations, there is a lack in literature concerning wood and charcoal from Coffea arabica. There are currently 5.6 billion coffee trees in a 2.3 million hectare area, generating residues, such as fruit bark and wood, which have potential as renewable fuels. Thus, the objective of this study was to evaluate the energetic potential of wood and charcoal from Coffea arabica in three cropping systems (organic, natural agroforestry and conventional) and two cultivars (Catuaí and Mundo Novo), by elemental chemical analysis. Carbonizations were carried out in an electric ove (muffle) with a final temperature of 450°C. The bioenergy use of wood from Coffea arabica, as well as of the charcoal from this plant, proved satisfactory based on inferences made from the elemental chemical composition of these fuels. In general, cultivation systems and cultivars little influenced the levels of carbon, hydrogen, oxygen and sulfur of wood and charcoal, as well as the ratios N/C, H/C and O/C.